Importancia de la facultad determinadora para la gestión de la administración tributaria. - Rivas Jimenez, Priscilla Elizabeth (My University, 2018)
In the present work we intend to make a brief explanation about the Determining Faculty of the Tax Administration. This research will be based on information obtained in different databases and mainly in the tax laws in force in Ecuador, such as the Organic Law of Internal Tax Regime (LORTI), Organic Tax Code. Therefore, the implemented methodology is of a documentary and bibliographic nature because we will obtain information on the subject treated from different sources. Within this power intervenes the taxpayer and the asset that makes up the State with the sole purpose that the Tax Administration through the Faculty Determining apply the corresponding procedures for the requirement of collection of taxes. In order to have knowledge about this faculty, the basic concepts that are related to the subject in question, generating fact, taxable base, obligated subjects and amount of the tax will be analyzed. The explanation of how and what is the correct way to make the determination, the expiration time, the documents to be used and their importance will be made. Thus it can be said that the Determining Faculty is the one that allows the tax administration to carry out the option of verification of compliance with the taxpayers' declaration, through the information obtained by the taxpayers.
En el presente trabajo se pretende realizar una breve explicación sobre la Facultad Determinadora de la Administración Tributaria. Esta investigación estará basada en información obtenida en diferentes bases de datos y principalmente en las leyes tributarias vigentes en el Ecuador, como lo es la Ley Orgánica de Régimen Tributario Interno (LORTI), Código Orgánico Tributario. Por lo tanto la metodología implementada es de carácter documental y bibliográfico debido a que obtendremos información del tema tratado de diferentes fuentes. Dentro de esta facultad interviene el sujeto pasivo y el activo que lo conforma el Estado con la única finalidad de que la Administración Tributaria a través de la Facultad Determinadora aplique los procedimientos correspondientes para el requerimiento del cobro de los impuestos. Para tener conocimiento sobre esta facultad se analizarán los conceptos básicos que están relacionados con el tema en mención, hecho generador, base imponible, sujetos obligados y cuantía del tributo. Se realizará la explicación de cómo y cuál es la manera correcta de realizar la determinación, el tiempo de caducidad, los documentos a utilizarse y su importancia. Es así que se puede decir que la Facultad Determinadora es la que permite a la administración tributaria realizar la opción de verificación del cumplimiento de la declaración de los contribuyentes, a través de la información obtenida por parte de los sujetos pasivos.
Keywords: TRIBUTOS; ADMINISTRACIÓN TRIBUTARIA; DOCTRINA TRIBUTARIA; FACULTAD DETERMINADORA